As disciplinas esportivas e as aulas práticas no curso de formação superior em educação física: perspectivas de graduandos - Cezar, Letícia Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In Brazil, physical education in schools came through the influence of gymnastic methods in the middle of 1841, and the superior formation only occurred in 1931, with the creation of the first Civil School of Physical Education of the State of São Paulo. Since then Physical Education has undergone several configurations, however, even if the area has materialized its own construction in the field of professional and epistemological performance, corporal practices still show as an important content for the initial formation of the future Physical Education professional that acts in school. Therefore, the objectives of this study were to investigate the reasons presented by the undergraduate students of Physical Education in the Licentiate area for the non-performance of the practical classes of the disciplines of Swimming, Karate and Handball, referring to the orientation to the corporal practices, as well as the importance which they attribute to teacher training. Eleven undergraduates from the Physical Education course of a Public University in the interior of the State of São Paulo participated in this study, in which the questionnaire and semistructure observation was applied as methodological instrument. The results found regarding reasons that lead the students to not participate in the practical classes were: muscle pain and injury, health problems, menstruation and discouragement. Already on the importance they attributed to the practical classes, all the participants answered that they consider them very important for the training. Based on these results, we can point out that what seems to make the participation of the graduates unfeasible is mostly linked to physical and health reasons, but although they consider the practical classes as an important factor, it still needs to be put in action, since participation directly implies their formation.

No Brasil, a Educação Física nas escolas chegou por meio das influências dos métodos ginásticos, em meados de 1841, e a formação superior só se deu em 1931, com a criação da primeira Escola Civil de Educação Física do Estado de São Paulo. Desde então a Educação Física passou por diversas configurações, todavia mesmo que a área tenha materializado uma construção própria no campo da atuação profissional e epistemológica, as práticas corporais ainda se mostram como um conteúdo importante para a formação inicial do futuro profissional de Educação Física que atua na escola. Com isso, os objetivos deste estudo foram investigar os motivos apresentados pelos graduandos de Educação Física, da área da Licenciatura, para a não realização das aulas práticas das disciplinas de Natação, Karatê e Handebol, referente a orientação às práticas corporais, bem como a importância que a atribuem para a formação docente. Participaram deste trabalho 11 licenciandos do curso de Educação Física de uma Universidade Pública do interior do Estado de São Paulo, no qual teve como instrumento metodológico a aplicação de questionário e observação semiestrutura. Os resultados encontrados relativos aos motivos que levam os alunos a não participarem das aulas práticas foram: dor muscular e lesão, problemas de saúde, menstruação e desânimo. Já sobre a importância que atribuíram às aulas práticas, todos os participantes responderam que as consideram muito importante para a formação. Com base nestes resultados, podemos apontar que o que parece inviabilizar a participação dos licenciandos está vinculado, em sua maioria, a motivos físicos e de saúde, mas que apesar deles considerarem as aulas práticas como um fator importante, é algo que ainda precisa ser posto em ação, visto que a participação implica diretamente em sua formação.
Keywords: Educação fisica - Ensino; Ensino superior; Esportes; Sports